Outcomes of Pectoralis Major Myocutaneous Flap for Reconstruction of Cheek Defects in Female Oral Squamous Cell Carcinoma Patients - Nahar, Munmun; Ataul Hasan, Mohammad; Haque, SK. Mozammel; Faisal, Seemran; Haider, Ismat Ara (Journal of Neonatal Surgery, 2025)
General objective of this study is to evaluate the outcome of Pectoralis Major Myo cutaneous flap in female OSCC patients for reconstruction of cheek defects in a tertiary care hospital of Bangladesh. Specific objectives were to assess the success and failure rate of Pectoralis Major Myo-cutaneous flaps (PMMFs) reconstruction of cheek defects developed due to surgical resection of female oral squamous cell carcinoma patients in a tertiary care hospital. Also to analyze the causes of failure and their association with complications and the association of complications with functional and aesthetic outcome. This prospective observational study carried out in department of OMFS of DDCH from January 2018 to September 2019 (19 months). Total 30 cases were selected and underwent operative treatment follow up was done at 1 month, 2 months and 3 months interval for evaluation of outcome. All the patients carried out composite resection with SOND or MRND and reconstruction by PMMC flap, failure rate of reconstruction was 26.7% which are defined by presence of major complications. Minor complications in 13(43.3%) which are managed conservatively. Major complications develop in 8(26.7%) cases like Partial flap necrosis in 3(37.5%) patients, wound infection in 1(12.5%), partial flap necrosis with intra-oral flap dehiscence in one (12.5%) patient and in 1 (12.5%) cases develop complete flap necrosis. Here major complications are significantly associated with increased age, presence of comorbidity, habit and increased flap size significantly. Also, rough surface texture, ugly scarring, speech impairment, dysphagia, restricted neck mobility also significantly associated with major complications.